Evaluation of the Total Amount of Phenol Groups in Complex Mixtures by Folin S and Orac-Fluorescein Methodologies - Lissi-Gervaso, E; Campos-Deramond, A; Campos-Deramond, A (Sociedad Chilena de Quimica, 2013)
The total number of phenolic HO groups in a mixture and their average reactivity are fundamental parameters in the evaluation of the capacity of the sample to remove potentially damaging free radicals. The total number of phenolic groups is generally determined by Folins method and several competitive experiments have been proposed to estimate the reactivity of the sample. Among those stand the Oxygen Radical Absorbance Capacity (ORAC) methodologies. However, when fluorescein is employed as target molecule (ORAC-FL methodology) the index is more related to the number of phenolic groups than to their average reactivity. In the present work it is shown that both indexes correlate with the number of phenolic groups in pure compounds and with the total number of reactive OH groups in complex mixtures (beverages, infusions, fruits and vegetables). This leads to a fair correlation between Folin s and ORAC-FL indexes in these samples.